Discharge path observation and the statistical characteristics of discharge paths for long–air gap discharge for in‐operation wind turbines. Issue 5 (12th February 2020) - Wen, Xishan; Deng, Yeqiang; Wang, Yu; Lan, Lei; Qu, Lu; Wang, Jian; Zhang, Tao; Wang, Huayun
Abstract: When a wind turbine is in normal operation, the blades are rotating, and this blade rotation may affect the process of lightning striking the wind turbine. To investigate this problem, long‐gap discharge tests are performed in this study. Moreover, a multiple physical parameter synchronous observation platform is designed for a scaled wind turbine. Long‐gap discharge tests of a static and rotary‐scaled wind turbine with blade tip‐electrode gap distances of 1 to 8 m are conducted, and the discharge paths under different gaps and wind turbine operating conditions are obtained. The characteristic parameters—arc shape upon discharge, lengths of the downward and upward leaders, blade angle at the moment of discharge, and angle of upward leader initiation—are statistically analyzed. The analysis of the aforementioned data indicates that rotation has opposite effects on the discharge characteristic parameters under short and long gap distances. According to the analysis, blade rotation reduces the space charge density of the corona discharge near the tip, which leads to an increase in the field strength near the blade tip and a decrease in the field strength away from the blade tip. Short and long gaps have different degrees of influence on discharge, which changes the difficulty of upward leader initiation at the blade tip and consequently alters the entire discharge process. The obtained results can provide a reference for the lightning protection of wind turbines.